2020
DOI: 10.3390/ani10040642
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Relocation during Rest Periods: Relocation Stress and Other Factors Influence Hair Cortisol Concentrations in Horses

Abstract: Horse transportation for temporary relocation during rest periods is a common and widespread practice among horse owners, either from sport competition or working tasks. This study aimed to determine the effect of a relocation period and the multiple factors associated with a rest period on hair cortisol concentrations (HCCs) in horses. Additionally, this study reports the seasonal effect on HCCs and hair growth over a year. Thirteen police horses, Pure Spanish stallions of various ages (5–13 y), were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…Therefore, six samples ( n = 6) per individual were collected during the study period (samples were chronologically identified as P1 to P6, corresponding, respectively, to late autumn–early winter, winter, spring, late spring–early summer, summer, and autumn). Samples were collected using the “shave-reshave” method, consisting of shaving the selected area at the beginning of the study and re-shaving the regrown hair in the same area after the time of interest has ended [ 27 ]. Specifically, a 7 × 7 cm area was caudally shaved to the sternum using an electric clipper as close as possible to the skin (0.5 ± 0.5 mm).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, six samples ( n = 6) per individual were collected during the study period (samples were chronologically identified as P1 to P6, corresponding, respectively, to late autumn–early winter, winter, spring, late spring–early summer, summer, and autumn). Samples were collected using the “shave-reshave” method, consisting of shaving the selected area at the beginning of the study and re-shaving the regrown hair in the same area after the time of interest has ended [ 27 ]. Specifically, a 7 × 7 cm area was caudally shaved to the sternum using an electric clipper as close as possible to the skin (0.5 ± 0.5 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The electric clipper was cleaned between individuals with 70% ethanol to avoid cross-contamination. Body location was selected to prevent potential injuries with the mount, to avoid visible aesthetic defects in the horses, and to avoid faecal and urine contamination [ 27 ]. Samples were stored in individually identified paper envelopes at room temperature until sample processing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring these physiological changes has been assessed with heart rate (HR) response, blood lactate concentrations, oxygen uptake in relation to exercise intensity [ 4 , 5 ], salivary, hair and blood cortisol [ 3 , 6 , 7 , 8 ], or immune cell proliferation [ 9 , 10 , 11 ]. However, they are all quite difficult measures to be assessed during regular equestrian competitions as riders and owners are unwilling to allow the experimental procedures to impact on the animal and affect their sport results.…”
Section: Introductionmentioning
confidence: 99%